Performance of sequence batch moving bed biofilm reactor under different operation cycle modes for domestic wastewater treatment - K.Azeez, Ghufran; S. Al-Rekabi, Wisam; T. Ibrahim, Husham (International Journal of Engineering and Technology, 2021)
Because of the rapid urbanization, the rate of surface water pollution is increasing daily due to the disposal of different wastewater in the water bodies leading to creating major impacts on humans and wildlife. Therefore, there is an urgent need to find a new treatment technology that can meet the challenges of increased sewage discharges and strictness in standard specifications for treated water and the lowest possible construction, maintenance, and operation costs while avoiding all the problems that arise from the use of the traditional technique of active sludge. Sequence Batch Moving Bed Biofilm Reactors (SBMBBR) technology has been developed to overcome these challenges, (SBMBBR) process is one of the most efficient and economical wastewater treatment systems. in our research. the Lab-scale of SBMBBR technology is constructed to treat domestic wastewater. The SBR unit is consist of; Primary clarifier of (150 L), an SBR reactor of (96 L) which were used to treated 80 L/d, at the MBB which used Kaldnes media, was utilized as a carrier in reactor at a media fill ratio equal to 50%. We Was optimize of five operations cyclic mode and choose The fourth cyclic mode is the best for the average efficiency of removal (COD, NH4+-N, TN, TP) was (98.132%), (97.642%), (82.255%), and (92.107%) respectively.Â Â